An optical chopper for generation of short X‐ray pulses to allow in‐house time‐resolved photocrystallography. (1st October 2014) - Kamiński, Radosław; Nottingham, Gary; Coppens, Philip
<x xml:space="preserve">Abstract</x> As part of a project to implement in‐house time‐resolved diffraction of short‐lifetime species, a fast shutter with a custom‐designed enclosure has been installed. The device is suitable for generation of X‐ray pulses with time lengths down to about 5 µs. The design does not require major modifications to commercially available diffractometer setups. Significant airflow, generated by the rotating chopper disc, which interferes with temperature control at the sample, has been eliminated by a compact enclosure, which does not interfere with sample monitoring and conditioning devices. It allows for full rotation of the diffractometer circles.